Knowledge, attitudes and practices of cervical cancer screening by health care providers in the Emana health area: Yaounde-Cameroon - Hortence, Fouedjio Jeanne; Sophie, Mawamba Sonfack; Brigitte, Wandji; Florent, Fouelifack Ymélé; Charlette, Nangue; ., Ngaroua; Dupont, Kemfang Ngowa Jean (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Gynaecological cancers and more particularly those of the cervix cause many victims in our country despite the many prevention tools that exist. The objective of this study was to assess the knowledge, attitudes and practices of providers on cervical cancer in the Emana health area. Methods: To achieve this objective, we conducted a cross-sectional study form the period from April 2nd to June 10th, 2019 in the health facilities of the Emana health area. Results: A total of 64 healthcare providers participated in the study, 03 gynecologists and obstetricians, 10 General practitioners, 30 state-certified nurses, 09 midwives, 12 nursing assistants. The majority of these providers had poor knowledge of the causes of the disease (25%), risk factors (34.4%), and means of prevention (39.1%), especially among state nurses (SRN), midwives, nursing assistants. (87.5%) had good knowledge of the clinical signs of the disease and were almost unanimous on the curability of this disease when discovered early (78.1%). The severity of the cancer was perceived by all; however, the practice of screening was low (10.9%). As for their personal screening practices, 73.1% (38/52) of female staff had never been screened. Conclusions: Even though the participants perceive the grave nature of the cervical cancer, the subsequent attitude and screening practices remain poor. The possible barrier to this is the insufficient continuous training and recycling of the health personnel. Emphasis should be laid on the methods of prevention of cervical cancer in the curricula of nurses and midwives in Cameroon.